22nd Annual Martin J. Forman Memorial Lecture - Sheeran, Josette (2012)
22nd Annual Forman Memorial Lecture Presentation "Public-Private Partnerships Innovating to End Malnutrition" by Josette Sheeran, World Economic Forum. December 4, 2012 at IFPRI.